If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 4x + 9 Reorder the terms: 12 = 9 + 4x Solving 12 = 9 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + -4x = 9 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + -4x = 9 + 0 12 + -4x = 9 Add '-12' to each side of the equation. 12 + -12 + -4x = 9 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = 9 + -12 -4x = 9 + -12 Combine like terms: 9 + -12 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75
| 3(x-6)-4(3x+1)=x-22 | | x*x+5x=155 | | 40+7x=12 | | iz^4+(5i+1)*z^2+4i+4=0 | | 3a+5b-2a+b= | | 3(y-1)+9=-6x+45 | | 7d-(6-2d)=-6 | | 4(a^3)-2(a^2)-7a-10=0 | | (x-4)(x-2)+1=0 | | 8-9x=17-16x | | 3x-0.5y=0 | | 5a*3b*2a= | | 5d*3e= | | 7a*2a= | | 4+16p+16p^2-36p=0 | | 10b+2=152-5b | | 9x+4y+6z-4x+5z-8y= | | 3k-3=12 | | 13y-3=8y+42 | | 3q=38 | | 125+20= | | 2x^2-x-25=0 | | 128=8t-8 | | 2(3x)=-18 | | 3n-11=22 | | -23p+23=23 | | 5x^2-34x-5=0 | | 8x+13=149 | | 48x^2+84x-432=0 | | 7-2x-(1-3x)/7=2-(2x-1)/3 | | 17x^2+14x-8=0 | | 13x^2-118x+240=0 |